2019
DOI: 10.21203/rs.2.14671/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human papillomavirus type 18 oncoproteins exert their oncogenicity in esophageal and tongue squamous cell carcinoma cell lines distinctly

Abstract: Increasing evidence indicates an etiological role of human papillomavirus (HPV) in head and neck cancers, particularly oropharyngeal squamous cell carcinoma (OPSCC). However, the association between HPV and other cancers, including esophageal and tongue remains unclear. This study delineated the molecular characteristics of HPV18 E6 and E7 in esophageal (EC109 and EC9706) and tongue (Tca83) cancer cell lines with reference to cervical cancer (HeLa). Overall, the HPV transcription profiles of esophageal and ton… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…We found that in ESCC, HPV18 oncoproteins do not exploit the same mechanism to promote cancer progression as known for cervical cancer. Instead of targeting pRB, E7 preferentially abrogates p130 in EC109 and EC9706, which are the HPV18 containing ESCC cell lines of Asian origin [ 16 ]. In addition to p53 and its downstream transcription transactivator [ 16 ], HPVE6 deregulates miR-125b, a microRNA that acts as a tumour suppressor [ 17 ].…”
Section: Association Between Oncoviruses and Oesophageal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…We found that in ESCC, HPV18 oncoproteins do not exploit the same mechanism to promote cancer progression as known for cervical cancer. Instead of targeting pRB, E7 preferentially abrogates p130 in EC109 and EC9706, which are the HPV18 containing ESCC cell lines of Asian origin [ 16 ]. In addition to p53 and its downstream transcription transactivator [ 16 ], HPVE6 deregulates miR-125b, a microRNA that acts as a tumour suppressor [ 17 ].…”
Section: Association Between Oncoviruses and Oesophageal Cancermentioning
confidence: 99%
“…Instead of targeting pRB, E7 preferentially abrogates p130 in EC109 and EC9706, which are the HPV18 containing ESCC cell lines of Asian origin [ 16 ]. In addition to p53 and its downstream transcription transactivator [ 16 ], HPVE6 deregulates miR-125b, a microRNA that acts as a tumour suppressor [ 17 ]. The downregulation of miR-125b may subsequently lead to activation of the Wnt/β-catenin signaling pathway, which is a critical pathway involved in cell differentiation, migration, proliferation, and cell death.…”
Section: Association Between Oncoviruses and Oesophageal Cancermentioning
confidence: 99%
“…The fundamental aspects of cancer biology consist of the cell dysregulation of proliferation, cell apoptosis [ 30 ], metastasis [ 31 ], gene aberration [ 32 ], anchorage-independent growth (AIG) [ 33 ], and tumor formation. Studies have found that HPV E6 mediates downregulation of p53, leading to DNA damage [ 34 – 36 ]. HPV E7 protein could downregulate the expression of p21 and p27, affect the cell cycle and make cells overproliferate, and result in inducing the occurrence of tumors [ 34 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that HPV E6 mediates downregulation of p53, leading to DNA damage [ 34 – 36 ]. HPV E7 protein could downregulate the expression of p21 and p27, affect the cell cycle and make cells overproliferate, and result in inducing the occurrence of tumors [ 34 , 36 , 37 ]. In our study, p21 was definitely downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of CBX3 by lentivirus‐mediated shRNA resulted in cell cycle delay by upregulating the P21 pathway (H. Zhang, Chen, Fu, Su, & Yang, 2018). It is documented that P21 acts as a downstream transactivation target of P53 (Boon et al, 2019). Moreover, a study conducted by Natsugoe et al (1999) revealed that P21 expression was positively correlated with P53 in ESCC tissues.…”
Section: Discussionmentioning
confidence: 99%